Die Tweetoringkerk as een van die N.G.-Gemeentes van Bloemfontein gedurende die Anglo-Boereoorlog 1899-1902 - R. M. Britz (Acta Theologica)
This article focuses on the local Dutch Reformed congregation of Bloemfontein during the Anglo-Boer War 1899-1902. As such it deals with a rather neglected, though very important, theme   concerning this destructive war in South Africa. In the Boer Republics the church and Christian faith played a constitutive role. The article thus makes a significant contribution to the recent research on the Anglo-Boer War. It tells the story of the life and times of a local congregation during war-time. Lead by the remaining consistory (elders and deacons), it survived the war. It had to adapt to the war situation and to a new dispensation when the Orange River Colony, replacing the Republic, was instituted during March 1900. This caused tension among the members of the congregation. Some accepted the new dispensation, and acted accordingly. Others were much more sceptical. Its members were involved in, and supported, the newly formed congregation in the concentration camp. It also related to its (non-white) Dutch Reformed Mission congregation in the same city.